PENGARUH ROA, EPS, DER, NPM TERHADAP RETURN SAHAM (STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019) - Sonia Gandhi Sonia; Mellinda - (JEBIM Prima, 2021)
This research was conducted on coal mining companies listed on the Indonesia Stock Exchange (IDX). The purpose of this research is to test and analyze the influence of Return On Assets (ROA), Earning PerShare (EPS), Debt to Equity Ratio(DER) and Net Profit Margin (NPM) on Share Return on coal mining companies listed on the Indonesia Stock Exchange in the period 2017-2019 either in a partial or simultaneous manner. The data in this company is secondary data obtained from the Indonesia Stock Exchange (IDX). There is a population in this study obtained from coal mining companies. There are 54 samples of issuers' financial statements using puposive sampling techniques.The results showed that : Return on Assets has a calculated t value of < t table, 0.466 < 1.99254 which means that Return on Assets is partially insignificant and insignificant in the disclosure of a company's Share Return. Earning Per Share has a calculated value of -t > -t table, -0.658 > -1.99254 which means that Earning Per Share is partially insignificant and insignificant in the disclosure of a company's Share Return. Debt to Equity Ratio has a calculated t value of > t table, -3,784 > -1.99254 which means that Debt to Equity Ratio is partially influential and significant in the disclosure of a company's Share Return. Net Profit Margin has a calculated t value of > t table, 4,483 > 1.99254 which means that Net Profit Margin is partially influential and significant in the disclosure of a company's Share Return. Return on Assets, Earning Per Share, Debt to Equity Ratio, Net Profit Margin simultaneously affects Stock Return.